Enhancing Financial Decision-Making in SMEs: The Role of Accounting Systems and Human Resource Competence in North Medan - Adi Harianto; Nurul Syafiqah Azman; Essia Ries Ahmed Abu Ries; Zakia Fadila; Tyus Windi Ayuni (Yayasan Bina Bisnis Nusantara Medan, 2025)
This research examines the influence of accounting system deployment and human resource proficiency on financial decision-making within small and medium enterprises (SMEs) in North Medan. The swift growth of SMEs in the region highlights the necessity of proficient financial management procedures, frequently shaped by the caliber of accounting systems and the competencies of human resources. A quantitative research methodology was employed to gather data via surveys from 150 owners and managers of SMEs in North Medan. The results indicate that the quality of financial decisions made by these businesses is greatly affected by both the use of a structured accounting system and the skills of the people who work there. The study shows how strong accounting processes improve financial openness and help with strategic decision-making. It also shows how talented workers can help with more accurate financial analysis and better long-term planning. The results indicate that small and medium-sized businesses (SMEs) need to spend money on both advanced accounting systems and training for their employees to improve their financial performance. This research enhances the comprehension of financial management in emerging economies and provides actionable recommendations for SMEs in North Medan to refine their financial decision-making processes